POSITIVE, NEGATIVE RULE AND APPLICATION - Nguyễn Đức Thuần; Phạm Quang Tùng; Hồ Thị Thu Sa (Tạp chí Khoa học Đại học Đà Lạt)
Positive and negative reasoning have been found to be very useful in practice, as is clear from the record of many real-life applications, especially in medicine. In this paper, we introduce the concepts of extended negative rule, minimal rule and their properties. Then, an algorithm to generate all minimal positive and minimal negative rules is introduced. Experimental results obtained on data sets from the UCI repository of machine learning databases and the result of an experiment performed on a real-world dataset, the teaching and learning database at Nhatrang University were discussed.